AGV routing : algorithms and tools - Toh, Zheng Cong (2016)
Automated Guided Vehicle (AGV) systems are widely used in container port operations for the transportation of containers. With the increase in AGV usage in a container port environment, it is important that the optimal routing algorithm is used to ensure a safe and efficient operations of the AGV system. This project aims to develop a simulation tool to simulate the operations of the container port environment. The tool facilitates the experimentation and evaluation of the routing algorithms, allowing users to customize settings for the simulation, such as the number of AGVs to employ or the routing algorithm to use. Also, this project examines the randomization approach, where randomization is introduced in routing algorithm. The purpose is to evaluate how randomization can affect the performance of the algorithm. Lastly, this project conducted experiments on various routing algorithms and dispatching methods. The results are evaluated to get the best algorithm and dispatching method for AGV operations.